2011
DOI: 10.1093/ecam/nep078
|View full text |Cite
|
Sign up to set email alerts
|

KIOM‐79, an Inhibitor of AGEs–Protein Cross‐linking, Prevents Progression of Nephropathy in Zucker Diabetic Fatty Rats

Abstract: Advanced glycation end products (AGEs) have been implicated in the development of diabetic complications, including diabetic nephropathy. KIOM-79, an 80% ethanolic extract obtained from parched Puerariae Radix, gingered Magnolia Cortex, Glycyrrhiza Radix and Euphorbia Radix, was investigated for its effects on the development of renal disease in Zucker diabetic fatty rats, an animal model of type 2 diabetes. In vitro inhibitory effect of KIOM-79 on AGEs cross-linking was examined by enzyme-linked immunosorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
3
21
0
1
Order By: Relevance
“…In the present study, BSA glycated with glycolaldehyde, Glycol-BSA was prepared, and was then employed to induce cross-links to collagen, which was measured using an ELISA system. 18) Glycated BSA with glycolaldehyde in the absence of collagen was employed to induce AGEs including cross-links, and the incorporation of [ 14 C] lysine into BSA was used to measure cross-link activity in our previous study. CA showed significantly potent activity in inhibiting cross-links to collagen compared with AG in the present assay, whereas AG as a positive control gave similar magnitude of potency against cross-links in ELISA assay (IC 50 , 67.8± 2.5 mM) and the previously reported radioactivity assay (IC 50 , 21.3± 1.4 mM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, BSA glycated with glycolaldehyde, Glycol-BSA was prepared, and was then employed to induce cross-links to collagen, which was measured using an ELISA system. 18) Glycated BSA with glycolaldehyde in the absence of collagen was employed to induce AGEs including cross-links, and the incorporation of [ 14 C] lysine into BSA was used to measure cross-link activity in our previous study. CA showed significantly potent activity in inhibiting cross-links to collagen compared with AG in the present assay, whereas AG as a positive control gave similar magnitude of potency against cross-links in ELISA assay (IC 50 , 67.8± 2.5 mM) and the previously reported radioactivity assay (IC 50 , 21.3± 1.4 mM).…”
Section: Discussionmentioning
confidence: 99%
“…The breaking assay on Glycol-BSA induced cross-links to collagen was performed according to the method by Kim et al 18) with some modifications. To confirm the breaking activity on Glycol-BSA induced cross-links to collagen, 1 mg/mL of Glycol-BSA was pre-incubated on 1.5 mg/mL of collagen for 24 h, and was then incubated in either the presence or absence of ALT-711 or CA at 37°C for 16 h. In detail, HRP labeled Glycol-BSA was pre-incubated on collagen-coated 96-well plates for 4 h, and the Glycol-BSA induced complexes with collagen were incubated in either the presence or absence of ALT-711 (Suchem Pharma Co., Wenzhou, China) or CA at 37°C for 16 h. After the unattached Glycol-BSA was washed in 0.05% PBST, breaking levels were detected using TMB substrate.…”
Section: Plant Materials and Preparation Of Camentioning
confidence: 99%
“…KIOM-79, which is a mixture of ethanol extracts from parched Puerariae radix, gingered Magnolia cortex, Glycyrrhiza radix, and Euphorbia radix, was developed based on the known function of each herb in treating diabetes. It has inhibitory effects on the development of renal disease in animal models of type 1 and type 2 diabetes (Kim et al, 2009). Previous studies have also shown that KIOM-79 has anti-diabetic effects, such as protection of betacells, reduced glucose in non-obese type 2 diabetic rats, inhibition of AGEs formation in vitro, and anti-inflammatory effects (Jeon et al, 2006;Kim et al, 2006Kim et al, , 2007aKim et al, , 2008aKim et al, ,b, 2009Kang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In our previous study, 700 plant extracts and phytochemicals were tested for inhibition of AGE formation by incubating glucose and bovine serum albumin (BSA) for 14 d; several extracts were shown to prevent diabetic complications, specifically nephropathy, cataract formation, and retinopathy in experimental animal models. [10][11][12] …”
Section: Abstract Advanced Glycation Endproduct; Receptor For Advancmentioning
confidence: 99%
“…[7][8][9] In our previous study, 700 plant extracts and phytochemicals were tested for inhibition of AGE formation by incubating glucose and bovine serum albumin (BSA) for 14 d; several extracts were shown to prevent diabetic complications, specifically nephropathy, cataract formation, and retinopathy in experimental animal models. [10][11][12] RAGE is a member of the immunoglobulin superfamily that consists of three extracellular immunoglobulin-like domains (i.e., V, C1, and C2), a transmembrane helical domain, and a short intracellular, negatively charged C-terminal tail that is indispensable for RAGE signaling. 13,14) The soluble form of RAGE (sRAGE) indirectly blocks AGE-RAGE binding.…”
mentioning
confidence: 99%